Penerapan Metode Transportasi Distribusi pada UD Kurnia Jaya - Ardhila Ayu Innana; Dea Putri Aulia; Muhammad Rizky Rizmawan; Tegar Andika Rahman Wijaya; Titis Purwaningrum (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2025)
This research aims to optimize the distribution of goods through the application of transportation methods at UD Kurnia Jaya. The main problem faced is how to minimize transportation costs in delivering rice to various agents. The Northwest Corner (NWC) method is used for the initial solution in processing supply and demand data. The results of the study show that the total minimum cost obtained for rice delivery is Rp 1,480,000 in one transportation. This study underscores the importance of applying transportation methods to improve distribution cost efficiency. It is hoped that this result can be a reference for MSMEs in managing logistics and increasing competitiveness through more optimal distribution management